Iron-indium-chromium microcrystal composite annular magnet yoke
By setting up a surface material layer with high indium content on the yoke parts and forming a microcrystalline ring-shaped composite structure of iron-indium chromium, the problem of lack of high-performance yokes in the prior art is solved, and self-lubricating and vibration-absorbing effects are achieved, and it is suitable for self-drive sensors and other fields.
Patent Information
- Application Number
- CN202510044260.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-11
- Publication Date
- 2025-04-01
AI Technical Summary
The prior art lacks relevant patent documents on iron-indium chromium microcrystalline composite annular yokes containing more than 50% indium and more than 60% indium and iron, and cannot meet the needs of high-performance yokes in the fields of self-drive sensors and other fields.
A layer of surface material layer containing more than 50% indium, more than 8% iron, and more than 1% chromium is set up on the upper surface of the yoke part, and an approximately spherical or approximately ellipsoidal iron-indium chromium crystals with a high distribution number are formed thereon to form a ring-shaped composite crystal crystal.
It realizes the high-performance self-lubricating and vibration-absorbing effect of iron-indium chromium microcrystal composite annular yoke, and is suitable for self-drive sensors and other fields, and has important application value and practical significance.
Smart Images

Figure CN119736715A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to an iron-indium-chromium microcrystalline composite annular magnetic yoke. Background Art
[0002] The magnetic yoke can be used for parts of self-driven sensors with a movement speed less than 0.1m / s. It can also be used for parts in the fields of magnetic fluid rheology or gas rheology.
[0003] The iron-indium-chromium microcrystalline composite annular magnetic yoke of the present invention is developed for a part of a self-driven sensor.
[0004] According to the results of literature and patent searches, there are currently no relevant patent documents reported in China regarding an iron-indium-chromium microcrystalline composite annular yoke containing more than 50% (wt%) indium and more than 60% (wt%) in indium and iron. Summary of the invention
[0005] The task of the present invention is to provide an iron-indium-chromium microcrystalline composite annular yoke, and the task of the present invention is achieved by the following technical scheme: a surface material layer is provided on the upper surface of the yoke part, the surface material layer contains more than 50% (wt%) indium, more than 8% (wt%) iron, more than 1% (wt%) chromium, and between 1% (wt%) and 3% (wt%) lanthanum, and between 0.5% (wt%) and 3% (wt%) bismuth; the upper surface of the surface material layer is flat and clean; the upper surface of the surface material layer is provided with a distribution number of ≥50 / (square micrometer) Nearly spherical or ellipsoidal FeInCr crystallites, each containing more than 50% (wt%) indium, more than 8% (wt%) iron and more than 1% (wt%) chromium, with a diameter or maximum length of less than 150nm, and in each FeInCr crystallite formation process, the static contact angle between the bottom part of the FeInCr crystallite and the surface material layer is less than 70°, and after cooling, the FeInCr crystallite and the surface material layer become one, and the interface width between each FeInCr crystallite and the surface material layer is greater than 15% of the maximum length of the FeInCr crystallite; an outer ring with a diameter greater than 120 nm and less than 2 μm, composed of no less than 8 FeInCr crystallites, with no FeInCr crystallites inside the ring, or less than or equal to 7 FeInCr crystallites are allowed to appear, but the sum of the interface areas between the FeInCr crystallite and the surface material layer in the ring is less than 35% of the inner area of the ring , forming annular composite microcrystals; adjacent annular composite microcrystals can share microcrystals, and many annular composite microcrystals are distributed on the upper surface of the surface material layer; the surface material layer of the part and the yoke part become one; forming an iron-indium-chromium microcrystal composite annular yoke.
[0006] The iron-indium-chromium microcrystalline composite annular yoke is realized by the following technical scheme: in a dry and clean air environment, the upper surface of the yoke part is ground, cleaned, degreased, and rusted, finely ground, ultrasonically cleaned, and dried, and then a flat and clean surface material layer is immediately covered on the finely ground surface, the surface material layer contains more than 50% (wt%) indium, more than 8% (wt%) iron, more than 1% (wt%) chromium, 1% (wt%) to 3% (wt%) lanthanum, and 0.5% (wt%) to 3% (wt%) bismuth, the size of the surface material layer is suitable for the upper surface of the yoke part, and the surface material layer fits well without wrinkles. Argon gas is passed through the air pipe through the regulating valve and into the empty box to remove the air in the empty box. After 10 minutes, the regulating valve is closed.Fix the heater on bracket B with screws, fix the interdigital transducer on the clamp with screws, fix the clamp on bracket A with screws, and fix the ultrasonic transmitter on bracket C with screws. The input power of the ultrasonic transmitter is 220V50Hz AC. Fix the yoke part on the heater with the attached clamp of the heater. Adjust the height and position of the clamp and bracket A, bracket B and bracket C to make the height and position of the yoke part, interdigital transducer and ultrasonic transmitter appropriate. The surface acoustic wave generated by the interdigital transducer when it is powered on can be transmitted to the upper surface of the yoke part. The ultrasonic wave output by the ultrasonic transmitter is aligned with the surface of the yoke part, and the ultrasonic transmitter is aligned with the yoke part. There is no direct contact with the surface of the yoke part; use a heater to heat the yoke part to 120℃~130℃. Preheating can reduce the micro cracks generated by laser beam heating; turn on the power, and the ultrasonic transmitter works normally; the rated power of the laser is greater than or equal to 1000W, adjust the laser beam power emitted by the laser and the appropriate area irradiated on the surface material layer; after the ultrasonic transmitter and the interdigital transducer work normally for 5 seconds, the pulse laser beam irradiates the surface material layer for 0.2 seconds, stops for 2 seconds, and the pulse laser beam irradiates the same position of the surface material layer again for 0.8 seconds; continue to pass argon gas for cooling; the ultrasonic transmitter and the interdigital transducer stop working; a distribution number of ≥50 / (square micrometer) is formed on the upper surface of the surface material layer Nearly spherical or ellipsoidal FeInCr crystallites, each containing more than 50% (wt%) indium, more than 8% (wt%) iron and more than 1% (wt%) chromium, with a diameter or maximum length of less than 150nm, and in each FeInCr crystallite formation process, the static contact angle between the bottom part of the FeInCr crystallite and the surface material layer is less than 70°, and after cooling, the FeInCr crystallite and the surface material layer become one, and the interface width between each FeInCr crystallite and the surface material layer is greater than 15% of the maximum length of the FeInCr crystallite; an outer ring with a diameter greater than 120 nm and less than 2 μm, composed of no less than 8 FeInCr crystallites, with no FeInCr crystallites inside the ring, or less than or equal to 7 FeInCr crystallites are allowed to appear, but the sum of the interface areas between the FeInCr crystallite and the surface material layer in the ring is less than 35% of the inner area of the ring , forming annular composite microcrystals; adjacent annular composite microcrystals can share microcrystals, and many annular composite microcrystals are distributed on the upper surface of the surface material layer; the surface material layer of the part and the yoke part become one; use a fine scraper to remove the surface material layer attached to each hole to form an iron-indium-chromium microcrystal composite annular yoke.
[0007] The shape and size of the iron indium chromium microcrystals of the iron indium chromium microcrystal composite annular magnetic yoke can be varied.
[0008] The shape and size of the annular composite microcrystals of the FeInCr microcrystal composite annular magnetic yoke can be varied.
[0009] After years of in-depth research, the inventors found that the vibration reduction and micro-friction wear reduction performance of the parts of the self-driven sensor with a moving speed less than 0.1m / s using the iron-indium-chromium microcrystalline composite annular yoke are quite different from the related yoke performance reported by most domestic and foreign scholars. The microcrystals of the iron-indium-chromium microcrystalline composite annular yoke contain more than 50% (wt%) indium, more than 8% (wt%) iron, and more than 1% (wt%) chromium, and have self-lubricating properties. The microcrystals are hollow composite annular and can store oil to form nano-scale micro-lubrication. Therefore, the study of the iron-indium-chromium microcrystalline composite annular yoke has important application value and practical significance.
[0010] Compared with the prior art, the related technologies of the iron-indium-chromium microcrystalline composite annular magnetic yoke of the present invention have significant improvements: ① The metallographic structure of the anti-fretting wear layer of the patent CN102918182A (published on 20130206) is mainly made of copper, and may also contain indium and iron. The content of iron in the copper-based alloy is 0.2wt%-0.5wt%, and the formation of the copper mixed grains is nano-sized and preferably oriented, which is supported or at least not hindered, so that the anti-fretting wear layer has a more uniform performance distribution. In the surface material layer of the present invention, the indium content exceeds 50% (wt%), the iron content exceeds 8% (wt%), and the chromium content exceeds 1% (wt%). Iron and indium are the main components. Therefore, the composition is significantly different, and the corresponding crystal performance arrangement technology is also significantly different. ② The patents "Indium-iron composite sphere microcrystalline composite layer (ZL201410481181.4)" and "Surface texture of indium-iron composite sphere microcrystalline composite layer (ZL201410481180.2)" have "the metallographic structure of the surface material layer has composite sphere microcrystalline units containing more than 50% (wt%) indium and the total content of indium and iron exceeding 55% (wt%), and the indium-iron composite sphere microcrystalline units are in an approximately regular close-packed array in rows or columns", which is obviously different from the composition of the surface material layer of the present invention "containing more than 50% (wt%) indium, more than 8% (wt%) iron and more than 1% (wt%) chromium", and the arrangement of the composite microcrystalline units is also obviously different.③ The patents "Indium-iron mesh ball composite microcrystalline composite layer (ZL201410481176.3)" and "Surface texture of indium-iron mesh ball composite microcrystalline composite layer (ZL201410481178.2)" are obviously different from the present invention, mainly reflected in: A. The "main component of the surface material layer is more than 50% (wt%) indium and the total content of indium and iron is more than 55% (wt%), and the indium-iron composite ball microcrystalline unit with a larger volume is composed of no less than 4 spherical grains or nearly spherical grains closely connected to form a grid, and the grid is composed of many densely packed single grains or no less than 2 spherical grains or nearly spherical grains closely connected to form a small volume indium-iron microcrystalline unit". wt%)", the composition is obviously different; B, the formation of the microcrystals of the present invention is "in the process of microcrystal formation, the contact angle between the bottom part of the microcrystal and the surface material layer is less than 70°, and the microcrystals and the surface material layer become one after cooling", which is obviously different; C, the present invention "is composed of no less than 8 microcrystals distributed to form an approximately closed outer ring with an diameter greater than 120 nm and less than 2 μm, and there are no microcrystals distributed inside the ring or the distribution area of the microcrystals is less than 10% of the area inside the ring, forming annular composite microcrystals; adjacent annular composite microcrystals can share microcrystals, and many annular composite microcrystals are distributed on the surface of the surface material layer", and the middle is empty, while "Indium-iron mesh ball composite microcrystal composite layer (ZL201410481176.3)", "Surface texture of indium-iron mesh ball composite microcrystal composite layer (ZL201410481178.2)" in "Indium-iron composite ball microcrystal units are distributed according to a certain rule to form a grid", and different grids are closely connected. ④ Patent: Preparation method of graphene-like copper indium sulfur nanosheet array film, CN201410098261.1, discloses a preparation method of graphene-like copper indium sulfur nanosheet array film in the field of nanomaterial preparation technology, the copper source used is monovalent copper salt, the indium source is indium chloride, the sulfur source is sulfur powder and thiourea, and the in-situ solvent thermal method is used to prepare a regular nanofilm. It is significantly different from the composition and structure of the present invention. Therefore, the related technology of the present invention has obvious and significant improvements.
[0011] The present invention realizes that the iron indium chromium microcrystals on the surface material layer contain more than 50% (wt%) indium, more than 8% (wt%) iron, and more than 1% (wt%) chromium, have self-lubricating properties, and the iron indium chromium microcrystals are in the shape of a hollow composite ring, which can store oil to form nano-scale micro-motion lubrication. Therefore, the grains of the iron indium chromium microcrystal composite annular yoke of the present invention have important application value and practical significance.
[0012] The invention has the advantages of being easy to use, simple in structure, strong in applicability, suitable in application cost and suitable for mass production. BRIEF DESCRIPTION OF THE DRAWINGS
[0013] Figure 1 This is a schematic diagram of the structure of the iron-indium-chromium microcrystalline composite annular yoke according to Example 1 of the present invention.
[0014] Figure 2 This is a schematic structural diagram of a sample manufacturing device for an iron-indium-chromium microcrystalline composite annular magnetic yoke according to Example 2 of the present invention.
[0015] Figure 3 This is a scanning electron microscope image of a surface material layer sample of the iron-indium-chromium microcrystalline composite annular yoke of Example 2 of the present invention.
[0016] In the accompanying drawings, 1-surface material layer, 2-yoke part, 3-argon gas, 4-air pipe, 5-regulating valve, 6-bracket A, 7-clamp, 8-interdigital transducer, 9-heater, 10-ultrasonic generator, 11-bracket B, 12-base, 13-empty box, 14-bracket C, 15-screw. DETAILED DESCRIPTION
[0017] The present invention will be further described below in conjunction with the accompanying drawings. Example
[0018] Figure 1 This is a schematic structural diagram of the iron-indium-chromium microcrystalline composite annular yoke of Example 1 of the present invention. In the figure, 1 is the surface material layer and 2 is the yoke part.
[0019] The iron-indium-chromium microcrystalline composite annular magnetic yoke of the present invention is characterized in that: a surface material layer is provided on the upper surface of the magnetic yoke part, the surface material layer contains more than 50% (wt%) indium, more than 8% (wt%) iron, more than 1% (wt%) chromium, and between 1% (wt%) and 3% (wt%) lanthanum, and between 0.5% (wt%) and 3% (wt%) bismuth; the upper surface of the surface material layer is flat and clean; the upper surface of the surface material layer is provided with a distribution number of ≥50 / (square micrometer) Nearly spherical or ellipsoidal FeInCr crystallites, each containing more than 50% (wt%) indium, more than 8% (wt%) iron and more than 1% (wt%) chromium, with a diameter or maximum length of less than 150nm, and in each FeInCr crystallite formation process, the static contact angle between the bottom part of the FeInCr crystallite and the surface material layer is less than 70°, and after cooling, the FeInCr crystallite and the surface material layer become one, and the interface width between each FeInCr crystallite and the surface material layer is greater than 15% of the maximum length of the FeInCr crystallite; an outer ring with a diameter greater than 120 nm and less than 2 μm, composed of no less than 8 FeInCr crystallites, with no FeInCr crystallites inside the ring, or less than or equal to 7 FeInCr crystallites are allowed to appear, but the sum of the interface areas between the FeInCr crystallite and the surface material layer in the ring is less than 35% of the inner area of the ring , forming annular composite microcrystals; adjacent annular composite microcrystals can share microcrystals, and many annular composite microcrystals are distributed on the upper surface of the surface material layer; the surface material layer of the part and the yoke part become one; forming an iron-indium-chromium microcrystal composite annular yoke. Example
[0020] Figure 2 Schematic diagram of the structure of a sample manufacturing device for an iron-indium-chromium microcrystalline composite annular magnetic yoke according to Example 2 of the present invention, Figure 3 This is a scanning electron microscope image of a surface material layer sample of the iron-indium-chromium microcrystalline composite annular magnetic yoke of Example 2 of the present invention. In the figure, 1 is the surface material layer, 2 is the magnetic yoke part, 3 is argon gas, 4 is the air pipe, 5 is the regulating valve, 6 is the bracket A, 7 is the clamp, 8 is the interdigital transducer, 9 is the heater, 10 is the ultrasonic generator, 11 is the bracket B, 12 is the base, 13 is the empty box, 14 is the bracket C, and 15 is the screw.
[0021] In a dry and clean air environment, the upper surface of the yoke part is ground, cleaned, degreased, derusted, finely ground, ultrasonically cleaned, and dried, and then a flat and clean surface material layer is immediately covered on the finely ground surface. The surface material layer contains more than 50% (wt%) indium, more than 8% (wt%) iron, more than 1% (wt%) chromium, between 1% (wt%) and 3% (wt%) lanthanum, and between 0.5% (wt%) and 3% (wt%) bismuth. The size of the surface material layer is suitable for the upper surface of the yoke part, and the surface material layer fits well without wrinkles.
[0022] The argon gas 3 is passed through the gas pipe 4 and the regulating valve 5 into the empty box 13 to exhaust the air in the empty box. After 10 minutes, the regulating valve 5 is closed.
[0023] Fix the heater 9 on the bracket B 11 with screws 15, fix the interdigital transducer 8 on the clamp 7 with screws, fix the clamp on the bracket A 6 with screws, and fix the ultrasonic transmitter 10 on the bracket C 14 with screws. The input power of the ultrasonic transmitter is 220V 50Hz AC. Fix the yoke part on the heater by the attached clamp of the heater 9. Adjust the height and position of the yoke part, the interdigital transducer and the ultrasonic transmitter appropriately by adjusting the position of the clamp and the height and position of the bracket A, bracket B and bracket C. The surface acoustic wave generated by the interdigital transducer when it is powered on can be transmitted to the upper surface of the yoke part. The ultrasonic wave output by the ultrasonic transmitter is aligned with the surface of the yoke part, and there is no direct contact between the ultrasonic transmitter and the surface of the yoke part. Heat the yoke part to 120℃~130℃ with the heater. Preheating can reduce the excitation. Micro cracks generated during beam heating; turn on the power, the ultrasonic transmitter works normally; the rated power of the laser is greater than or equal to 1000W, adjust the laser beam power emitted by the laser and the appropriate area irradiated on the surface material layer; after the ultrasonic transmitter and the interdigital transducer work normally for 5 seconds, the pulsed laser beam irradiates the surface material layer for 0.2 seconds, stops for 2 seconds, and the pulsed laser beam irradiates the same position of the surface material layer again for 0.8 seconds; continue to pass argon gas for cooling; the ultrasonic transmitter and the interdigital transducer stop working; form a distribution number ≥50 / (square micrometer) on the upper surface of the surface material layer Nearly spherical or ellipsoidal FeInCr crystallites, each containing more than 50% (wt%) indium, more than 8% (wt%) iron and more than 1% (wt%) chromium, with a diameter or maximum length of less than 150nm, and in each FeInCr crystallite formation process, the static contact angle between the bottom part of the FeInCr crystallite and the surface material layer is less than 70°, and after cooling, the FeInCr crystallite and the surface material layer become one, and the interface width between each FeInCr crystallite and the surface material layer is greater than 15% of the maximum length of the FeInCr crystallite; an outer ring with a diameter greater than 120 nm and less than 2 μm, composed of no less than 8 FeInCr crystallites, with no FeInCr crystallites inside the ring, or less than or equal to 7 FeInCr crystallites are allowed to appear, but the sum of the interface areas between the FeInCr crystallite and the surface material layer in the ring is less than 35% of the inner area of the ring , forming annular composite microcrystals; adjacent annular composite microcrystals can share microcrystals, and many annular composite microcrystals are distributed on the upper surface of the surface material layer. The scanning electron microscope image of the sample is as follows Figure 3 As shown; the surface material layer of the part and the yoke part become one; the surface material layer attached to each hole is removed with a fine scraper to form an iron-indium-chromium microcrystalline composite annular yoke.
Claims
1. Iron-indium-chromium microcrystalline composite annular yoke, characterized by : A surface material layer is provided on the upper surface of the yoke part, the surface material layer contains more than 50% (wt%) indium, more than 8% (wt%) iron, more than 1% (wt%) chromium, and between 1% (wt%) and 3% (wt%) lanthanum, and between 0.5% (wt%) and 3% (wt%) bismuth; the upper surface of the surface material layer is flat and clean; on the upper surface of the surface material layer, there are ≥50 / (square micrometer) of approximately spherical or approximately ellipsoidal iron indium chromium microcrystals distributed, each of which contains more than 50% (wt%) indium, more than 8% (wt%) iron, and more than 1% (wt%) chromium, and has a diameter or maximum length of less than 150nm, and in the formation process of each iron indium chromium microcrystal, the static contact angle between the bottom part of the iron indium chromium microcrystal and the surface material layer is less than 70°, and after cooling, the iron indium chromium microcrystal and the surface material layer become one, and the interface width of each iron indium chromium microcrystal and the surface material layer is greater than 15% of the maximum length of the iron indium chromium microcrystal An outer ring with a diameter greater than 120 nm and less than 2 μm is formed by the distribution of no less than 8 FeInCr crystallites, and there are no FeInCr crystallites inside the ring, or the number of FeInCr crystallites less than or equal to 7 is allowed, but the sum of the interface areas between the FeInCr crystallites in the ring and the surface material layer is less than 35% of the inner area of the ring, forming an annular composite crystallite; adjacent annular composite crystallites can share crystallites, and many annular composite crystallites are distributed on the upper surface of the surface material layer; the surface material layer of the part and the yoke part become one; forming an FeInCr crystallite composite annular yoke.
2. The iron-indium-chromium microcrystalline composite annular yoke according to claim 1, characterized in that: In a dry and clean air environment, the upper surface of the yoke part is ground, cleaned, degreased, and derusted, finely ground, ultrasonically cleaned, and dried, and then a flat and clean surface material layer is immediately covered on the finely ground surface. The surface material layer contains more than 50% (wt%) indium, more than 8% (wt%) iron, more than 1% (wt%) chromium, 1% (wt%) to 3% (wt%) lanthanum, and 0.5% (wt%) to 3% (wt%) bismuth. The size of the surface material layer is suitable for the upper surface of the yoke part, and the surface material layer fits well without wrinkles. Argon gas is passed through the air pipe through the regulating valve and into the empty box to exhaust the air in the empty box. After 10 minutes, the regulating valve is closed. Fix the heater on bracket B with screws, fix the interdigital transducer on the clamp with screws, fix the clamp on bracket A with screws, and fix the ultrasonic transmitter on bracket C with screws. The input power of the ultrasonic transmitter is 220V 50Hz AC. Fix the yoke part on the heater with the attached clamp of the heater. Adjust the height and position of the clamp and bracket A, bracket B and bracket C to make the height and position of the yoke part, interdigital transducer and ultrasonic transmitter appropriate. The surface acoustic wave generated by the interdigital transducer when it is powered on can be transmitted to the upper surface of the yoke part, and the working output of the ultrasonic transmitter is The ultrasonic wave emitted is aimed at the surface of the yoke part, and the ultrasonic transmitter has no direct contact with the surface of the yoke part; the yoke part is heated to 120℃~130℃ by a heater, and preheating can reduce the micro cracks generated by laser beam heating; the power is turned on, and the ultrasonic transmitter works normally; the rated power of the laser is greater than or equal to 1000W, and the power of the laser beam emitted by the laser and the appropriate area irradiated on the surface material layer are adjusted; after the ultrasonic transmitter and the interdigital transducer work normally for 5 seconds, the pulse laser beam irradiates the surface material layer for 0.2 seconds, stops for 2 seconds, and the pulse laser beam irradiates the same position of the surface material layer again for 0.8 seconds; continue to pass argon gas for cooling; The ultrasonic transmitter and the interdigital transducer stop working; a nearly spherical or ellipsoidal FeInCr microcrystal with a distribution number of ≥50 / (square micrometer) is formed on the upper surface of the surface material layer, each FeInCr microcrystal contains more than 50% (wt%) indium, more than 8% (wt%) iron, and more than 1% (wt%) chromium, with a diameter or maximum length less than 150nm, and in each FeInCr microcrystal formation process, the static contact angle between the bottom part of the FeInCr microcrystal and the surface material layer is less than 70°, and after cooling, the FeInCr microcrystal and the surface material layer become one, and the interface width between each FeInCr microcrystal and the surface material layer is greater than 15% of the maximum length of the FeInCr microcrystal; an outer ring with a diameter greater than 120 nm and less than 2 μm is formed by the distribution of not less than 8 FeInCr microcrystals, and there is no FeInCr microcrystal inside the ring, or the number of FeInCr microcrystals less than or equal to 7 is allowed, but the sum of the interface areas of the FeInCr microcrystals in the ring and the surface material layer is less than 35% of the inner area of the ring , forming annular composite microcrystals; adjacent annular composite microcrystals can share microcrystals, and many annular composite microcrystals are distributed on the upper surface of the surface material layer; the surface material layer of the part and the yoke part become one; use a fine scraper to remove the surface material layer attached to each hole to form an iron-indium-chromium microcrystal composite annular yoke.
Citation Information
Patent Citations
Multi-layer plain bearing having an anti-fretting layer
CN102918182A
Method for preparing graphene structure-like copper-indium-sulfur nanosheet array membrane
CN103819099A
Surface Texture of Indium Iron Mesh Ball Composite Microcrystalline Composite Layer
CN104228188B
Indium iron composite ball microcrystalline composite layer
CN104228189B
Indium-iron grid-shaped spherical composite microcrystal composite layer
CN104228206A